1996
DOI: 10.1073/pnas.93.6.2557
|View full text |Cite
|
Sign up to set email alerts
|

Progression of human breast cancers to the metastatic state is linked to hydroxyl radical-induced DNA damage.

Abstract: Hydroxyl radical damage in metastatic tumor DNA was elucidated in women with breast cancer, and a comparison was made with nonmetastatic tumor DNA. The damage was identified by using statistical models of modified base and Fourier transform-infrared spectral data. The modified base models revealed a greater than 2-fold increase in hydroxyl radical damage in the metastatic tumor DNA compared with the nonmetastatic tumor DNA. The metastatic tumor DNA also exhibited substantially greater base diversity than the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
142
1
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(153 citation statements)
references
References 33 publications
(19 reference statements)
9
142
1
1
Order By: Relevance
“…Each point was a highly discriminating representation of an individual DNA structure in that spatially and visually close points had Ͻ3% average spectral difference over the range 1750-700 cm Ϫ1 (5). The core cluster of metastatic tumor DNA points was substantially larger than the core cluster of nonmetastatic tumor DNA points and significantly more diverse (P ϭ 0.003).…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…Each point was a highly discriminating representation of an individual DNA structure in that spatially and visually close points had Ͻ3% average spectral difference over the range 1750-700 cm Ϫ1 (5). The core cluster of metastatic tumor DNA points was substantially larger than the core cluster of nonmetastatic tumor DNA points and significantly more diverse (P ϭ 0.003).…”
mentioning
confidence: 98%
“…In a recent study (5), the transformation of primary breast tumors to the metastatic state was shown to involve a Ͼ2-fold increase in ⅐OH damage in DNA, as indicated by modified nucleotide base models comprising mutagenic 8-hydroxyadenine (6) and the putatively nonmutagenic ring-opened product 4,6-diamino-5-formamidopyrimidine (fapyadenine; refs. [7][8][9][10][11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the observation that several carcinogens cause oxidative DNA damage, with increased 8-OHdG levels, in laboratory animals before tumor formation occurs and that tumor progression is linked to this type of damage strongly support the hypothesis that oxidative DNA base modifications play an important role in carcinogenesis. 26 To our knowledge, this is the first study investigating the expression level of 8-OHdG in multistep vulvar carcinogenesis. We observed a progressive increase in the levels of 8-OHdG from normal to VIN to invasive carcinomas (Figure 2 and Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 90%